Comprehensive insights into the function and molecular and pharmacological regulation of neuron-derived orphan receptor 1, an orphan receptor - Hong, Hongxiang; Su, Jianbin; Huang, Chao; Lu, Xu; Cui, Zhiming (Frontiers in Pharmacology, 2022)
Neuron-derived orphan receptor 1 (NOR1), also called nuclear receptor subfamily 4 group A member 3 (NR4A3), is a nuclear receptor belonging to the NR4A family. Since no endogenous ligand has been identified to date, NOR1 is also referred to as an orphan receptor. NOR1 is expressed in a variety of cells and tissues, including neurons, vascular smooth muscle cells, T lymphocytes, dendritic cells, tumor cells, heart, liver, and pancreas. Because NOR1 was first identified in apoptotic neurons, it is functionally associated with the regulation of cell migration and the growth of neuronal synapses. In-depth studies have shown that NOR1 can be edited by the immediate early gene and functions as a transcription factor. NOR1 has been shown to be rapidly induced by a number of stimulants including growth factors, fatty acids, and neurotransmitters. Elevated NOR1 levels may be involved in a number of pathophysiological processes. These include regulation of cellular apoptosis and regeneration, neuron formation, contextual fearing memory, inflammation, vascular smooth muscle proliferation, insulin secretion, and tumor development, whereby NOR1 mediates the pathogenesis of numerous diseases such as cerebral ischemia, depression, post-traumatic stress disorder, atherosclerosis, abdominal aortic aneurysm, cardiac hypertrophy, diabetes, osteoarthritis, rheumatoid arthritis, and cancer. However, to date, comprehensive insights into the function of NOR1 are not available in sources published online. In this review, we provide a brief overview of the function and molecular and pharmacological regulation of NOR1 in various pathological or physiological conditions to advance the development of NOR1 as a novel target for disease treatment.